Zinc sulfide thin films deposited by chemical bath: Tuning consideration of structural, optical band gap, and electrical properties for CIGS solar cells application - Arsad A.Z.; Bahrudin M.S.; Arzaee N.A.; Rahman M.N.A.; Chau C.F.; Abdullah S.F.; Zuhdi A.W.M. (Elsevier Ltd, 2025)
Zinc sulfide (ZnS) is widely employed in a solar cell structure as a buffer layer due to its excellent physical and chemical properties. ZnS elements discovered in the earth's crust are safe. This study examined the performance characteristics of ZnS thin films deposited on soda lime glass substrate via chemical bath deposition. The ZnS thin films were annealed at temperatures of 300, 400, and 500 C in a vacuum environment. XRD showed the ZnS thin films with high annealing temperatures are composed of a wurtzite structure. Increased annealing temperature improved crystallization, average crystallite sizes, film thickness, and low dislocation density as well as lattice strain. The FESEM analysis reveals that the morphology of annealed thin film at high temperatures has larger grains compared to the deposited films. EDS spectra confirm that zinc and sulfur are present in the ZnS thin film. Annealed films have an average transmission of 20?50 % in the visible spectrum of 300?1100 nm. Films exhibit 103 cm resistivity, and the bulk carrier density ranges between 1012 and 1014 cm?3. The annealed film at 500 C has a direct band gap of 3.47 eV, a resistivity of 1.79 ? 103 cm, and a bulk concentration of 1.19 ? 1014 cm?3. All ZnS thin films have n-type conductivity. ? 2024 Elsevier Ltd and Techna Group S.r.l.